An Analysis of Language and Tourism Development; A Socioligusitic Approach - Aminah, Nur; Hamjah, Hamjah Diha; Putraidi, Karyawan (YAYASAN HAMJAH DIHA bekerjasama dengan PENA INSTITUTE, 2022)
Bonjeruk village has historical and cultural potential. So the youths felt that the Bonjeruk that had once triumphed as one of the central government in the Netherlands even the sub-district at that time was centered in the village of bonjeruk,thus of course the Bonjeruk territory to the Kute region in the southern part of the island of Lombok, the Pujut sub-district which is now also part of the Bonjeruk electricity, which means that the Bonjeruk Managing has never really been the center of government. This research used qualitative-descriptive method. Technique of data collection is carried out through observation, interview methods and documentation. Technique of analyzing data analysis in qualitative research is a process of categorization, description, and synthesis. Those activities are data reduction, data display, and conclusion drawing/verification. Based on those statements, the researcher divides the activity in analyzing data into three activities, they are data reduction, data display, and conclusion drawing. The results of this study indicate that there is a relationship between English language skills and tourism development. Case studies that focus on researching the relationship between language and tourism by conducting observations, interviews and documentation. As described in Nawamin Prachanant's 2012 research entitled Needs Analysis on English Language Use in Tourism Industry. that the ability to speak English is needed at work, especially for speaking in English. because the key to the sustainability of a tourism lies in the ability to speak to promote the tourism place. thus making the language especially English as one of the supporting factors for the development of a tourism.